Timed Digital Cascade Control of Gas-filled Tubes - Beszedes, Bertalan (IEEE International Conference and Workshop in Óbuda on Electrical and Power Engineering (Online), 2024)
The aim of this paper is to present the operation, construction, design and scientific background of a Nixie tube display, microcontroller and BCD decoder controlled RTC clock with RTC interface. The paper describes the control of old TTL devices with today's modern microcontrollers, and discusses the discharge phenomena of tubes filled with a gas mixture and the control principles of this type of display tube. The analogue circuits required for operation are also described, as well as the reception and synchronisation of the atomic clock signal.